An Empirical View on Local Residents’ Perceptions towards E-Government in Kyrgyzstan - Maksüdünov, Azamat (Studies of Transition States and Societies, 2024)
Digital transformation in the public sector has been the focus of academic studies for the last two decades. According to the literature, countries’ efforts towards digitalization vary both across countries and within regions of each country. Although the starting points may differ, this process has yet to be completed in any country. It is evident that various obstacles and problems are still being encountered. Along with major obstacles such as inadequate infrastructure and limited financial and human resources, the willingness of residents to adopt e-government services is also a significant factor to consider. In this context, the main purpose of this paper is to evaluate residents’ perceptions towards e-government services in Kyrgyzstan. Primary data was collected by administering a structured questionnaire to 325 residents. The results indicate that perceived functional benefits, perceived service response, and availability of resources significantly impact (p<0.05) residents’ adoption of e-government services. Significant differences have been observed in residents’ perceptions towards the dependent and independent variables of the study, based on demographic characteristics such as marital status, income, experience using e-government services, and area of residence. This study can provide valuable insights for public policy related to digital transformation. A deeper understanding of users’ behavior can provide a reliable foundation for making managerial and marketing decisions that can help overcome this problem as a barrier to digital transformation.